2014
DOI: 10.1039/c4cp01891e
|View full text |Cite
|
Sign up to set email alerts
|

Selective adsorption ofl-serine functional groups on the anatase TiO2(101) surface in benthic microbial fuel cells

Abstract: To help design bacteria-friendly anodes for unmediated benthic microbial fuel cells (MFCs), we explore the role of anatase TiO2(101) surface biocompatibility in selecting the functional groups of the levo-isomer serine (L-Ser), which contains carboxyl, hydroxyl, and amino groups in a single molecule. By performing total energy calculations and molecular dynamics simulations based on a density-functional tight-binding method, we find that at room temperature, the surface should be active for biomolecules with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The effect of water has been investigated in the case of the adsorption on TiO 2 of a serine molecule, an amino acid slightly larger than glycine. It was found that the presence of water weakens the O-Ti bonds and H-bonds existing between the -COO À /-OH groups and the surface [310]. The effect of the grafting of an organic molecule on the surface gap has also been explored and was found to be negligible in the case of an acetic acid molecule adsorbed either on a crystalline oxide surface (anatase (101), rutile (110) and (B)-TiO 2 (001)) or on an amorphous one ((a)-TiO 2 ) [311].…”
Section: Supported or Embedded Systemsmentioning
confidence: 99%
“…The effect of water has been investigated in the case of the adsorption on TiO 2 of a serine molecule, an amino acid slightly larger than glycine. It was found that the presence of water weakens the O-Ti bonds and H-bonds existing between the -COO À /-OH groups and the surface [310]. The effect of the grafting of an organic molecule on the surface gap has also been explored and was found to be negligible in the case of an acetic acid molecule adsorbed either on a crystalline oxide surface (anatase (101), rutile (110) and (B)-TiO 2 (001)) or on an amorphous one ((a)-TiO 2 ) [311].…”
Section: Supported or Embedded Systemsmentioning
confidence: 99%
“…Due to the biological reaction that occurs on the surface of the anode electrodes, the biocompatibility of anode electrode materials is essential in determining the power output of MFCs [85,86,87]. The biocompatibility of electrode materials can be summarized via two aspects.…”
Section: Development Of Graphene-modified Electrodes In Microbial mentioning
confidence: 99%
“…Notably, the incorporation result in synergy from diverse aspects. For example, the incorporation of zero‐dimensional nanoparticles, such as Au,44 MnO 2 ,45 TiO 2 ,44, 46 Pd,47 Fe 2 O 3 ,37a and Fe 3 O 4, 37b can enhance the performance of MFCs by increasing the surface area and interface roughness of the anode. Similarly, the addition of one‐dimensional and two‐dimensional materials can also result in the enhancement of the overall performance.…”
Section: Anode Manipulationmentioning
confidence: 99%